Application of Insurance Agent Services at PT. Takaful FamilyAsuration with Android-Based Incremental Method: Aplikasi Pelayanan Agen Asuransi Pada Pt. Asuransi Takaful Keluarga Dengan Metode Incremental Berbasis Android - Arik Apriyani Arik Apriyani; Ahmad Zuhdi; Abdul Rochman (Intelmatics, 2022)
Insurance Agent Service Application With Android-Based Incremental Method is a development in terms of service for agents at PT. Family Takaful Insurance. This information system has been running on a website-based basis, namely the TAIS (Takaful Agency Information System) application. However, when this website-based application is used, it is still impractical for agents working in the field. So far, when agents want to see the information, they have to use a computer or laptop, which sometimes gets stuck with the connection. With this Android-Based Incremental Method, it is made so that users, namely agents, can easily obtain agency information while working in the field. This application contains agency information, policy status made, contests to agents, and product illustrations.